Eisenmangelanämie und Anämie der chronischen Erkrankungen = Iron deficiency anemia and anemia of chronic disorders - Metzgeroth, Georgia; Hastka, Jan (Der Internist, 2015)
Hypochromic-microcytic anemias are characterized by a hemoglobin deficiency of the erythrocytes. The main reason for the insufficient hemoglobin synthesis is, with exception of thalassemia and a few other rare conditions, primarily a disorder of iron metabolism. Differential diagnostic considerations are focused on iron deficiency anemia, with approximately 80 % the most common form of anemia worldwide. Iron deficiency anemia shows a particularly high prevalence in developing countries, but is also in industrialized Western countries the most common cause of anemia. Infants, toddlers, premenopausal or pregnant women, and elderly people are at particularly high risk of iron deficiency anemia. The most important differential diagnosis for iron deficiency anemia is the anemia of chronic disorders (ACD). This anemia is caused by a disturbance of iron utilization (functional iron deficiency), in which iron absorption and iron release, as a nonspecific defense mechanism, is blocked to restrict iron availability for the inflammatory process but also withhold iron from the erythropoiesis. ACD is not rare, but plays a significant role in hospitalized patients and in the elderly. The differentiation between ACD and iron deficiency anemia is highly important from a clinical point of view, due to different types of further management. The cause for iron deficiency should be clarified in each case, whereas the etiology for ACD is often obvious. The standard treatment of iron deficiency anemia is oral iron supplementation. Intravenous iron application is reserved for problem patients. The best treatment for ACD is the elimination of the underlying chronic disorder. In case of persistent ACD, red blood cell transfusions, erythropoietin, and intravenous iron are used therapeutically.